High-tensile single-component bio-based epoxy structural adhesive as well as preparation method and application thereof
By constructing a quaternary synergistic epoxy matrix crosslinking network and using a low-temperature, low-speed mixing process, a high-tensile-strength single-component bio-based epoxy structural adhesive was prepared, which solved the problems of insufficient tensile strength and poor storage stability in the existing technology. This enabled the application of high-performance, environmentally friendly structural adhesives, making them suitable for the lightweighting and integration process of automobiles.
Patent Information
- Application Number
- CN202611124178.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-08-25
AI Technical Summary
Existing single-component epoxy structural adhesives suffer from insufficient tensile strength, imbalance between strength and toughness, poor storage stability, weak construction compatibility, and difficulty in achieving a balance between environmental performance and mechanical properties.
A quaternary synergistic epoxy crosslinking network was constructed using bisphenol A type liquid epoxy resin, rubber-modified epoxy resin, polyurethane-modified epoxy resin and cashew phenol-based epoxy blend. Combined with a latent curing system, dehydrating agent and thixotropic agent, a high tensile strength single-component bio-based epoxy structural adhesive was prepared by low temperature and low speed mixing process.
It achieves improved tensile strength, shear strength and peel strength, significantly enhances the fatigue strength and impact resistance of structural components, extends shelf life, is compatible with automotive automated adhesive application production lines, reduces energy consumption, and broadens the application range.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application belongs to the field of epoxy resin adhesive technology, and more specifically, relates to a high tensile strength single-component bio-based epoxy structural adhesive, its preparation method and application. Background Technology
[0002] Lightweighting and integrated manufacturing have become core trends in the automotive industry. Using adhesives instead of traditional rivets can effectively reduce vehicle weight, accelerate integrated manufacturing processes, and promote the large-scale application of adhesives in automotive structural bonding. Among these, bio-based epoxy structural adhesives, with their core advantages of being renewable and environmentally friendly, align perfectly with the automotive industry's green development needs. Furthermore, the epoxy system itself possesses excellent bonding reliability, thermal stability, resistance to corrosion, and high mechanical strength, making it widely used for bonding automotive sheet metal and structural components. When used in conjunction with spot welding, laser welding, and other processes, it can significantly improve the fatigue strength, overall stiffness, and impact resistance of structural components.
[0003] One-component epoxy structural adhesives have become the mainstream type of adhesive used in automotive structural bonding due to their convenient application, rapid curing via heating, and compatibility with automated production lines. However, existing one-component epoxy structural adhesives generally suffer from poor adhesion, poor toughness, and insufficient tensile strength.
[0004] Therefore, it is crucial to provide a single-component bio-based epoxy structural adhesive with multi-substrate bonding capability, high toughness, and high tensile strength. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this application is to provide a high tensile strength single-component bio-based epoxy structural adhesive, its preparation method and application, aiming to solve the problems of insufficient tensile strength, imbalance of strength and toughness, poor storage stability, weak construction adaptability, and difficulty in balancing environmental protection and mechanical properties of single-component epoxy structural adhesives.
[0006] To achieve the above objectives, in a first aspect, this application provides a high tensile strength single-component bio-based epoxy structural adhesive, comprising, by weight, 50-70 parts of bisphenol A type liquid epoxy resin, 23-47 parts of composite toughening agent, 0.5-1.5 parts of epoxy diluent, 2-6 parts of dehydrating agent, 10-15 parts of filler, 3-7 parts of thixotropic agent, 4-6 parts of latent curing agent, and 0.5-1.5 parts of curing accelerator; The aforementioned composite toughening agent includes a rubber-modified epoxy resin, a polyurethane-modified epoxy resin, and a cashew nut shell epoxy blend; wherein the aforementioned cashew nut shell epoxy blend is obtained by blending cashew nut shell epoxy phenolic resin with cashew nut shell bifunctional glycidyl ether epoxy resin.
[0007] Preferably, the mass ratio of the above-mentioned cashew phenol-based epoxy phenolic resin to the above-mentioned cashew phenol-based difunctional glycidyl ether epoxy resin is (1.5~2.5):1.
[0008] Preferably, the blending temperature is 40℃~50℃, the rotation speed is 300rpm~450rpm, and the blending time is 1h~3h.
[0009] Preferably, the weight ratio of the above-mentioned rubber-modified epoxy resin, the above-mentioned polyurethane-modified epoxy resin and the above-mentioned cashew phenol-based epoxy blend is (15~25):(3~7):(5~15).
[0010] Preferably, the epoxy value of the above-mentioned bisphenol A type liquid epoxy resin is 0.3eq / 100g to 0.6eq / 100g.
[0011] Preferably, the rubber-modified epoxy resin is selected from one or more of carboxylated nitrile rubber-modified epoxy resin and core-shell rubber-modified epoxy resin.
[0012] Preferably, the epoxy value of the polyurethane modified epoxy resin is 0.37 eq / 100g to 0.5 eq / 100g.
[0013] Preferably, the epoxy diluent is selected from one or more of benzyl glycidyl ether, butyl glycidyl ether, ethyl octyl caprylate, polypropylene glycol diglycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether.
[0014] Preferably, the dehydrating agent is calcium oxide.
[0015] Preferably, the filler is calcium carbonate.
[0016] Preferably, the thixotropic agent is silica.
[0017] Preferably, the aforementioned latent curing agent is dicyandiamide.
[0018] Preferably, the curing accelerator is an imidazole curing agent.
[0019] Secondly, this application provides a method for preparing the above-mentioned high tensile strength single-component bio-based epoxy structural adhesive, comprising the following steps: S1. Mix the above-mentioned bisphenol A type liquid epoxy resin and the above-mentioned composite toughening agent at 60℃~80℃ according to the formula to obtain a resin mixture; S2. Mix the above resin mixture with the above dehydrating agent, the above filler and the above thixotropic agent at 50°C to 60°C to obtain a mixed base material; S3. After cooling the above mixed base material to 0℃~15℃, mix it with the above latent curing agent and the above curing accelerator to obtain the mixed adhesive, which is the above high tensile single-component bio-based epoxy structural adhesive.
[0020] Preferably, in step S1, the mixing speed is 800 rpm to 950 rpm and the time is 30 min to 90 min.
[0021] Preferably, in step S2, the mixing speed is 500 rpm to 650 rpm and the time is 10 min to 60 min.
[0022] Preferably, in step S3, the mixing speed is 300 rpm to 450 rpm and the time is 10 min to 60 min.
[0023] Preferably, the above preparation method further includes vacuum degassing of the above mixed rubber compound.
[0024] Preferably, the conditions for the above-mentioned vacuum degassing treatment are: vacuum degree ≤ -0.1MPa, temperature 40℃~60℃, and time 0.5h~1.5h.
[0025] Thirdly, this application provides an application of the above-mentioned high tensile strength single-component bio-based epoxy structural adhesive in automotive structural bonding.
[0026] In summary, the technical solutions conceived in this application have the following main technical advantages compared with the prior art: (1) The high tensile strength single-component bio-based epoxy structural adhesive provided in this application constructs a quaternary synergistic epoxy matrix crosslinking network by bisphenol A type liquid epoxy resin, rubber modified epoxy resin, polyurethane modified epoxy resin and cashew phenol-based epoxy blend. The crosslinking structure is optimized at the molecular level, breaking the bottleneck of the traditional structural adhesive's imbalance between strength and toughness, where increased toughness leads to insufficient tensile strength and increased shear strength leads to increased brittleness. The resulting structural adhesive has excellent tensile strength, shear strength and peel strength, and can withstand the dynamic and static high loads of automotive structural components, significantly improving the fatigue strength and impact resistance of structural components. Among them, the cashew phenol-based epoxy blend, as a toughening component, can also give the product the advantages of being renewable, environmentally friendly and low-toxic without reducing the mechanical properties of the structural adhesive, which is in line with the green, low-carbon and sustainable development trend of the automotive industry, taking into account both environmental protection and reliability.
[0027] (2) The high tensile strength single-component bio-based epoxy structural adhesive provided in this application, through the synergistic compounding effect of multiple epoxy components with latent curing system, dehydrating agent, thixotropic system and other components, extends the product's room temperature storage period to more than 6 months (up to 8 months in optimal form), solving the pain points of short storage period and easy thickening failure of existing single-component bio-based epoxy adhesives, and meeting the needs of industrial production, long-distance transportation and long-term storage. At the same time, it endows the structural adhesive with excellent anti-sagging and coating uniformity (anti-sagging length ≤1mm), can be adapted to automotive automated coating production lines without on-site mixing, and can achieve medium-temperature rapid curing, significantly reducing energy consumption and improving production efficiency.
[0028] (3) The high tensile strength single-component bio-based epoxy structural adhesive provided in this application has excellent bonding performance to commonly used automotive substrates such as steel, aluminum and composite materials. It can improve the traditional anchoring connection, reduce the weight of the vehicle body, simplify the assembly process, promote the lightweighting and integration of automobiles, and broaden the application scope of bio-based epoxy structural adhesives in high-end automotive structural bonding.
[0029] (4) The preparation method of the high tensile strength single-component bio-based epoxy structural adhesive provided in this application uses a low temperature and low speed mixing process to disperse the mixed base material and the latent curing system, thereby inhibiting the pre-reaction of the curing agent and epoxy matrix from the source, ensuring the storage stability of the structural adhesive. At the same time, the increased viscosity of the adhesive under low temperature conditions achieves a grinding-like dispersion effect, avoiding powder agglomeration and the introduction of air bubbles, ensuring the high density and mechanical properties of the adhesive layer, giving full play to the high tensile strength and high toughness advantages of the multi-component epoxy system, and taking into account both product performance and industrial production requirements. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0031] In the description of this application, it should be understood that the term "and / or" describes a relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.
[0032] In the description of the embodiments in this application, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or design options. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0033] In the description of the embodiments in this application, unless otherwise stated, "multiple" means two or more.
[0034] This application provides a high tensile strength single-component bio-based epoxy structural adhesive, comprising, by weight, 50-70 parts of bisphenol A type liquid epoxy resin, 23-47 parts of composite toughening agent, 0.5-1.5 parts of epoxy diluent, 2-6 parts of dehydrating agent, 10-15 parts of filler, 3-7 parts of thixotropic agent, 4-6 parts of latent curing agent, and 0.5-1.5 parts of curing accelerator; The aforementioned composite toughening agent includes a rubber-modified epoxy resin, a polyurethane-modified epoxy resin, and a cashew nut shell epoxy blend; wherein the aforementioned cashew nut shell epoxy blend is obtained by blending cashew nut shell epoxy phenolic resin with cashew nut shell bifunctional glycidyl ether epoxy resin.
[0035] In some embodiments, the mass ratio of the above-mentioned cashew phenol-based epoxy phenolic resin to the cashew phenol-based bifunctional glycidyl ether epoxy resin is (1.5~2.5):1.
[0036] In some embodiments, the blending temperature is 40°C to 50°C, the rotation speed is 300 rpm to 450 rpm, and the blending time is 1 hour to 3 hours. For example, the blending temperature is 40°C, 45°C, 50°C, etc.; the rotation speed is 300 rpm, 320 rpm, 350 rpm, 400 rpm, 420 rpm, 450 rpm, etc.; and the blending time is 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc. In some embodiments, to ensure more thorough mixing, the cashew nut shell phenolic epoxy resin can be heated first, and then blended with the cashew nut shell phenolic difunctional glycidyl ether epoxy resin.
[0037] In some embodiments, the weight ratio of the above-mentioned rubber-modified epoxy resin, polyurethane-modified epoxy resin and cashew phenol-based epoxy blend is (15~25):(3~7):(5~15).
[0038] This application constructs a multi-component synergistic epoxy network with bisphenol A type liquid epoxy resin as the rigid matrix, rubber-modified epoxy resin as the toughening reinforcing phase, polyurethane-modified epoxy resin as the flexible buffer phase, and cashew phenol-based epoxy blend as the bio-based reinforcing phase, achieving synergistic optimization of rigidity, toughness, and interfacial bonding at the molecular structure level. Simultaneously, by precisely controlling the latent curing system, dehydrating agent, and thixotropic system formulation, it effectively solves the long-standing technical bottlenecks of traditional single-component epoxy structural adhesives, such as the imbalance between strength and toughness, insufficient storage stability, and poor application compatibility. Through the synergistic effect between components, it ultimately achieves simultaneous improvement in high tensile strength, high fracture toughness, and good storage stability, perfectly meeting the high-end application requirements of high-performance, environmentally friendly, and automated construction of structural adhesives in the process of automotive lightweighting integration.
[0039] In some embodiments, the aforementioned high tensile strength single-component bio-based epoxy structural adhesive, by weight, comprises 55-65 parts of bisphenol A type liquid epoxy resin, 35-40 parts of composite toughening agent, 0.5-1.5 parts of epoxy diluent, 2-6 parts of dehydrating agent, 10-15 parts of filler, 3-7 parts of thixotropic agent, 4-6 parts of latent curing agent, and 0.5-1.5 parts of curing accelerator. The weight ratio of the rubber-modified epoxy resin, polyurethane-modified epoxy resin, and cashew nut phenol-based epoxy blend in the composite toughening agent is (18-25):(4-7):(8-15).
[0040] In some embodiments, the epoxy value of the bisphenol A type liquid epoxy resin is 0.3 to 0.6 eq / 100g. For example, the bisphenol A type liquid epoxy resin may be selected from, but is not limited to, one or more of epoxy resins E-55, E-51, E-44, and E-42.
[0041] In some embodiments, the aforementioned rubber-modified epoxy resin is selected from one or more of carboxylated nitrile butadiene rubber-modified epoxy resin and core-shell rubber-modified epoxy resin. In this application, the aforementioned carboxylated nitrile butadiene rubber-modified epoxy resin refers to a product of modifying epoxy resin with a carboxyl-containing nitrile butadiene rubber (such as terminal carboxyl-terminated liquid nitrile butadiene rubber CTBN). In some embodiments, the aforementioned carboxylated nitrile butadiene rubber-modified epoxy resin is a CTBN-modified epoxy resin.
[0042] In some embodiments, the epoxy value of the polyurethane-modified epoxy resin is 0.37~0.5 eq / 100g.
[0043] In some embodiments, the epoxy diluent is selected from one or more of benzyl glycidyl ether, butyl glycidyl ether, ethyl octyl caprylate, polypropylene glycol diglycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether.
[0044] In some embodiments, the dehydrating agent is calcium oxide.
[0045] In some embodiments, the filler is calcium carbonate. This application does not specifically limit the type of calcium carbonate; it can be aqueous heavy calcium carbonate, hydrophobic light calcium carbonate, or activated calcium carbonate.
[0046] In some embodiments, the thixotropic agent is silica. In some embodiments, the silica is fumed silica, including hydrophobic fumed silica and hydrophilic fumed silica.
[0047] In some embodiments, the aforementioned latent curing agent is dicyandiamide.
[0048] In some embodiments, the curing accelerator is an imidazole curing agent. In some embodiments, the imidazole curing agent includes, but is not limited to, one or more of 2-methylimidazole, 2-ethylimidazole, modified imidazole compounds, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole.
[0049] On the other hand, this application also provides a method for preparing the above-mentioned high tensile strength single-component bio-based epoxy structural adhesive, comprising the following steps: S1. Mix the bisphenol A type liquid epoxy resin and the composite toughening agent at 60℃~80℃ according to the formula to obtain a resin mixture; S2. Mix the above resin mixture with dehydrating agent, filler and thixotropic agent at 50℃~60℃ to obtain a mixed base material; S3. After cooling the above mixed base material to 0℃~15℃, mix it with a latent curing agent and a curing accelerator to obtain a mixed adhesive, which is the above high tensile strength single-component bio-based epoxy structural adhesive.
[0050] In some embodiments, in step S1, the mixing speed is 800 rpm to 950 rpm and the mixing time is 30 min to 90 min. In some embodiments, in step S2, the mixing speed is 500 rpm to 650 rpm and the mixing time is 10 min to 60 min.
[0051] In some embodiments, in step S3, the mixing speed is 300 rpm to 450 rpm and the time is 10 min to 60 min. This application disperses the mixed base material and the latent curing system (including latent curing agent and curing accelerator) through a low-temperature, low-speed mixing process, which inhibits the pre-reaction between the curing agent and the epoxy matrix from the source, ensuring the storage stability of the structural adhesive. At the same time, it utilizes the increased viscosity of the adhesive under low-temperature conditions to achieve a grinding-like dispersion effect, avoiding powder agglomeration and the introduction of air bubbles, ensuring the high density and consistent mechanical properties of the adhesive layer, fully leveraging the high tensile strength and high toughness advantages of the multi-component epoxy system, and taking into account both product performance and industrial production requirements.
[0052] It is understood that those skilled in the art can make adaptive adjustments to the above-mentioned mixing speed and time based on the type of actual production equipment, production scale, material viscosity, ambient temperature, etc. As long as the adjusted process conditions can make the raw materials mix evenly, they are all within the scope of protection of this application.
[0053] In some embodiments, the preparation method further includes vacuum degassing of the mixed rubber compound. In some embodiments, the conditions for the degassing treatment are: vacuum degree ≤ -0.1 MPa, temperature 40℃~60℃, and time 0.5h~1.5h.
[0054] The single-component bio-based epoxy structural adhesive provided in this application possesses advantages such as high tensile strength, high fracture toughness, and good storage stability, meeting the high-end application requirements for high-performance, environmentally friendly, and automated construction of structural adhesives in the process of automotive lightweighting integration. Based on this, this application also provides the application of this high-tensile-strength single-component bio-based epoxy structural adhesive in automotive structural bonding.
[0055] It should be understood that materials of the same or similar type, model, quality, properties, or function as the reagents and instruments used in the following embodiments can be used to implement this application. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available. Specifically, some raw material information involved in the specific embodiments of this application is as follows: Bisphenol A type liquid epoxy resin: purchased from Baling Petrochemical, grade 128; Rubber-modified epoxy resin: Core-shell rubber-modified epoxy resin, purchased from Huiya New Materials, brand name HY-T054; Polyurethane modified epoxy resin: purchased from Zhuzhou Shilin Polymer, brand name SL-3403; Cashew nut phenol-based epoxy blend: Cashew nut phenol-based epoxy phenolic resin (purchased from Cardläte, brand name: LITE-547LV) was heated to 40°C and then mixed with cashew nut phenol-based bifunctional glycidyl ether epoxy resin (purchased from Cardläte, brand name: NC-514) at a mass ratio of 6:4. The mixture was stirred at 50°C for 1 hour to ensure uniform blending. After cooling, the cashew nut phenol-based epoxy blend was obtained.
[0056] Epoxy diluent: methyl octyl decanoate, purchased from Maclean, brand name G-906406; Dehydrating agent: calcium oxide, purchased from Taihe New Materials, brand name YH-1250; Filler: Calcium carbonate, purchased from Jinjian New Materials, brand name Jinjian Nano Calcium Type A, with an average particle size of 0.07μm; Thixotropic agent: silica, purchased from Evonik, grade R805; Latent curing agent: dicyandiamide, purchased from Longchuang New Materials, brand name H-3005, particle size D50 is 4μm; Curing accelerator: Modified imidazole compound, purchased from Ajinomoto, brand name PN-40.
[0057] The following are examples and comparative examples: Examples 1-5 The formulations (by weight) of the single-component bio-based epoxy structural adhesives provided in Examples 1-5 of this application are listed in Table 1.
[0058]
[0059] Comparative Examples 1-8 The formulations (by weight) of the single-component bio-based epoxy structural adhesives provided in Comparative Examples 1 to 8 of this application are listed in Table 2.
[0060]
[0061] The preparation method of the single-component bio-based epoxy structural adhesive provided in Examples 1-5 and Comparative Examples 1-8 above includes the following steps: Step (1): Under 70°C, bisphenol A type liquid epoxy resin, rubber modified epoxy resin, polyurethane modified epoxy resin, cashew phenolic epoxy blend and epoxy diluent are stirred and mixed at 900 rpm for 1 hour to obtain a resin mixture. Step (2): At 55°C, the above resin mixture, dehydrating agent, filler, and thixotropic agent are stirred and mixed for 0.5 h under vacuum degree ≤0.1MPa and rotation speed 600rpm until the powder is completely dispersed and there is no agglomeration, thus obtaining the mixed base material; Step (3): Reduce the temperature of the above mixed base material to 5°C, then add the latent curing agent and curing accelerator, and stir and mix for 0.5 h under vacuum degree ≤0.1MPa and rotation speed 400rpm to obtain the mixed adhesive. Step (4): The above mixed adhesive is vacuum degassed for 1 hour under vacuum conditions of ≤0.1MPa and 50℃, and the target product is obtained by discharging the material, which is a single-component bio-based epoxy structural adhesive.
[0062] Comparative Example 9 The formulation of the single-component bio-based epoxy structural adhesive provided in this comparative example is the same as that in Example 1. The difference is that the mixed base material was not cooled in step (3). The specific operation is as follows: the mixed base material, latent curing agent and curing accelerator are stirred and mixed for 0.5h under the conditions of vacuum degree ≤0.1MPa and rotation speed 400rpm at 55℃ to obtain the mixed adhesive.
[0063] The performance of the single-component bio-based epoxy structural adhesives prepared in Examples 1-5 and Comparative Examples 1-9 was tested. The curing conditions were 120℃ for 40 min, and the test methods are as follows: a) Tensile strength: Tested according to the method provided in GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0064] b) Elongation at break: Tested according to the method provided in GB / T 528-2009.
[0065] c) Shear strength: The steel-to-steel shear strength was tested according to the method provided in GB / T 7124-2008, with Q235 steel sheet as the adherend; the aluminum-to-aluminum shear strength was tested according to the method provided in GB / T 7124-2008, with 6061 aluminum alloy sheet as the adherend.
[0066] d) T-peel strength: Tested according to the method provided in GB / T 2791-1995 "Test method for T-peel strength of adhesives".
[0067] e) Storage period at room temperature: The test shall be conducted in accordance with the method provided in HG / T 3075 2003 "Regulations on Packaging, Marking, Transportation and Storage of Adhesive Products".
[0068] f) Sagging resistance length: The test shall be conducted in accordance with the method provided in GB / T 31113-2014 "Determination of Sagging Resistance of Adhesives".
[0069] The performance test results of the single-component bio-based epoxy structural adhesives prepared in Examples 1-5 and Comparative Examples 1-9 of this application are shown in Table 3.
[0070]
[0071] The test results (Table 3) show that, compared with comparative examples 1-8, the structural adhesive prepared in this application exhibits superior performance in key indicators such as tensile strength, elongation at break, shear strength, T-peel strength, room temperature storage life, and anti-sagging properties. The reason for this may be that the single-component bio-based epoxy structural adhesive prepared in this application constructs a synergistic adhesive network through a quaternary compound of bisphenol A type liquid epoxy resin, rubber-modified epoxy resin, polyurethane-modified epoxy resin, and cashew phenol-based epoxy blend. This optimizes the crosslinking structure at the molecular level, ensuring high tensile strength while significantly improving elongation at break and peel strength. It completely solves the core defects of traditional structural adhesives, such as imbalance between strength and toughness, high brittleness, and low peel strength, enabling it to withstand dynamic loads and impact resistance requirements of automotive structural components. Simultaneously, by optimizing and adjusting the dosage of components such as dehydrating agents, fillers, and thixotropic agents, the synergistic effect between components is fully utilized, ensuring the long-term storage stability of the structural adhesive from the source and endowing the adhesive with excellent anti-sagging properties, fully meeting the requirements of automated automotive adhesive application. This resulted in a single-component bio-based epoxy structural adhesive with high tensile strength, high fracture toughness, excellent storage stability, and good construction compatibility.
[0072] Comparing Example 1 and Comparative Example 9, it was found that the structural adhesive prepared in Example 1 has a shelf life of more than 8 months at room temperature, which is much longer than that of Comparative Example 9 (≤3 months). The reason for this may be that Comparative Example 9 did not use a low-temperature (0℃~15℃) mixing process when mixing the base material, curing agent, and curing accelerator. This caused the dicyandiamide curing agent to undergo a pre-crosslinking reaction with the epoxy group, and the activity of the curing agent was consumed prematurely. As a result, the structural adhesive gradually thickened and lost its fluidity during room temperature storage, significantly shortening its shelf life. In contrast, this application effectively inhibits the pre-reaction between dicyandiamide and epoxy group through a low-temperature, low-speed stirring and calcium oxide dehydration synergistic system, thus ensuring the long-term storage stability of the structural adhesive from the source.
[0073] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A high tensile strength single-component bio-based epoxy structural adhesive, characterized in that, By weight, it includes 50-70 parts of bisphenol A type liquid epoxy resin, 23-47 parts of composite toughening agent, 0.5-1.5 parts of epoxy diluent, 2-6 parts of dehydrating agent, 10-15 parts of filler, 3-7 parts of thixotropic agent, 4-6 parts of latent curing agent, and 0.5-1.5 parts of curing accelerator. The composite toughening agent comprises a rubber-modified epoxy resin, a polyurethane-modified epoxy resin, and a cashew nut shell epoxy blend; wherein the cashew nut shell epoxy blend is obtained by blending cashew nut shell epoxy phenolic resin with cashew nut shell bifunctional glycidyl ether epoxy resin.
2. The high tensile strength single-component bio-based epoxy structural adhesive according to claim 1, characterized in that, The mass ratio of the cashew phenol-based epoxy phenolic resin to the cashew phenol-based bifunctional glycidyl ether epoxy resin is (1.5~2.5):
1.
3. The high tensile strength single-component bio-based epoxy structural adhesive according to claim 1, characterized in that, The blending temperature is 40℃~50℃, the rotation speed is 300rpm~450rpm, and the time is 1h~3h.
4. The high tensile strength single-component bio-based epoxy structural adhesive according to claim 1, characterized in that, The weight ratio of the rubber-modified epoxy resin, the polyurethane-modified epoxy resin, and the cashew phenol-based epoxy blend is (15~25):(3~7):(5~15).
5. The high tensile strength single-component bio-based epoxy structural adhesive according to claim 4, characterized in that, The bisphenol A type liquid epoxy resin has an epoxy value of 0.3 eq / 100g to 0.6 eq / 100g; and / or, The rubber-modified epoxy resin is selected from one or more of carboxylated nitrile rubber-modified epoxy resin and core-shell rubber-modified epoxy resin; and / or, The epoxy value of the polyurethane-modified epoxy resin is 0.37 eq / 100g to 0.5 eq / 100g.
6. The high tensile strength single-component bio-based epoxy structural adhesive according to claim 1, characterized in that, The epoxy diluent is selected from one or more of benzyl glycidyl ether, butyl glycidyl ether, ethylene oxide methyl octyl caprylate, polypropylene glycol diglycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether; and / or, The dehydrating agent is calcium oxide; and / or, The filler is calcium carbonate; and / or, The thixotropic agent is silica; and / or The latent curing agent is dicyandiamide; and / or, The curing accelerator is an imidazole-based curing agent.
7. A method for preparing a high tensile strength single-component bio-based epoxy structural adhesive as described in any one of claims 1 to 6, characterized in that, The steps include the following: S1. Mix the bisphenol A type liquid epoxy resin and the composite toughening agent at 60℃~80℃ according to the formula to obtain a resin mixture; S2. Mix the resin mixture, the dehydrating agent, the filler, and the thixotropic agent at 50°C~60°C to obtain a mixed base material; S3. After cooling the mixed base material to 0℃~15℃, mix it with the latent curing agent and the curing accelerator to obtain a mixed adhesive, which is the high tensile strength single-component bio-based epoxy structural adhesive.
8. The preparation method according to claim 7, characterized in that, In step S1, the mixing speed is 800 rpm to 950 rpm and the time is 30 min to 90 min; and / or, In step S2, the mixing speed is 500 rpm to 650 rpm and the time is 10 min to 60 min; and / or, In step S3, the mixing speed is 300 rpm to 450 rpm and the time is 10 min to 60 min.
9. The preparation method according to claim 7, characterized in that, The preparation method further includes vacuum degassing of the mixed adhesive; The conditions for the vacuum degassing treatment are: vacuum degree ≤ -0.1MPa, temperature 40℃~60℃, and time 0.5h~1.5h.
10. The application of a high tensile strength single-component bio-based epoxy structural adhesive as described in any one of claims 1 to 6 in automotive structural bonding.